Perforins Expression by Cutaneous Gamma Delta T Cells - O'Neill, Katelyn; Pastar, Irena; Tomic-Canic, Marjana; Strbo, Natasa (Frontiers in Immunology, 2020)
Gamma delta (GD) T cells are an unconventional T cell type present in both the epidermis and the dermis of human skin. They are critical to regulating skin inflammation, wound healing, and anti-microbial defense. Similar to CD8+ cytotoxic T cells expressing an alpha beta (AB) TCR, GD T cells have cytolytic capabilities. They play an important role in elimination of cutaneous tumors and virally infected cells and have also been implicated in pathogenicity of several autoimmune diseases. T cell cytotoxicity is associated with the expression of the pore forming protein Perforin. Perforin is an innate immune protein containing a membrane attack complex perforin-like (MACPF) domain and functions by forming pores in the membranes of target cells, which allow granzymes and reactive oxygen species to enter the cells and destroy them. Perforin-2, encoded by the gene MPEG1, is a newly discovered member of this protein family that is critical for clearance of intracellular bacteria. Cutaneous GD T cells express both Perforin and Perforin-2, but many questions remain regarding the role that these proteins play in GD T cell mediated cytotoxicity against tumors and bacterial pathogens. Here, we review what is known about Perforin expression by skin GD T cells and the mechanisms that contribute to Perforin activation.